Romantic Love: Neither Sexist Nor Heterosexist - Caraway, Carol (Philosophy & theology, 1987)
Feminists and gay liberationists condemn romantic love as an inherently sexist and heterosexist institution which requires sexist idealizations and heterosexual desire. I argue that although romantic love in contemporary Western societies often includes sexist idealizations and heterosexual desire, those elements are not necessary constituents of the concept of romantic love. The crucial elements in romantic love are concern, admiration, the desire for reciprocation, and the passion for union, none of which require either sexist idealizations or heterosexual sexual desire.